Representasi Identitas Medan dalam Iklan Lapo Tuak - Hizkia Sumihar Hutabarat; Anisa Puteri Br Bukit; Christ Jhon Widianto; Yosue Alberto Sijabat (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study explores how social identity is constructed and represented in the promotion of traditional tuak drinking culture through the social media content of Atlas Medan, a modern lapo tuak café. Utilizing Social Identity Theory, this research investigates how cultural symbols and regional slang—particularly from Batak and Medan cultures—are employed to reinforce a local identity while appealing to a young demographic (ages 20–40). Using semiotic analysis on 50 selected Instagram posts, this study decodes how Atlas Medan merges traditional and modern elements to craft a compelling digital presence. The findings indicate that the strategic use of Batak songs, Medan slang, and community-oriented visuals fosters a sense of belonging among viewers, effectively branding the café as a hub of local cultural pride. This research contributes to a broader understanding of local identity-based branding and the role of digital media in preserving yet reinterpreting traditional cultural elements in urban settings.